Detection of A1 and A2 milk in Tiruchirappalli district using TANUVAS A1A2 detect kit - vembu iyer, jayalalitha; K, Shining Thomas; PN, Richard Jagatheesan (Indian Journal of Dairy Science, 2022)
Milk contributes a vital role in nutritional security in most of the countries of the world. Recently a debate is going on worldwide that, A1 milk is harmful and A2 milk is beneficial. Though there was no supporting clinical evidence to claim these, milk is selling in the name of A2 milk for high cost without proper identification in the field level. To address this issue to both consumer and producers, scientists are in a position to rule out the A1 and A2 milk. In this study TANUVAS A1A2 detect kit was used in the A1 or A2 type milk with dried blood or milk spot. 31 samples were collected from farms and individual farmers from different places of Tiruchirappalli district. All the samples were analysed with the ready to use primer based PCRÂ  test TANUVAS A1A2 detect kit. This study revealed that 20% of the crossbred cows, 78.95% of the indigenous breed cows, 66.67 % of non descriptive cows and 100 percent of the buffaloes had A2A2 genotype. The results of this study is giving the fact that, milk needs to be checked out with proper test like TANUVAS A1A2 detect before claiming for A2 milk.